A case of successful conversion surgery for locally advanced pancreatic cancer with synchronous triple cancer of the lung and esophagus: a case report - Junya Mita; Tomohiro Iguchi; Norifumi Iseda; Kazuki Takada; Kosuke Hirose; Naoko Miura; Takuya Honboh; Yasunori Emi; Tetsuro Akashi; Seiya Kato; Noriaki Sadanaga; Hiroshi Matsuura (Surgical Case Reports)
Abstract Background The number of reports of multiple primary cancer (MPC) is increasing because of the advancement in diagnostic imaging technology. However, the treatment strategy for MPCs involving pancreatic cancer is controversial because of the extremely poor prognosis. We herein report a patient with synchronous triple cancer involving the pancreas, esophagus, and lung who underwent conversion surgery after intensive chemotherapy for unresectable locally advanced pancreatic cancer. Case presentation A 59-year-old man was admitted to our hospital with epigastric pain, anorexia, and weight loss. Computed tomography and upper gastrointestinal endoscopy revealed that the patient had synchronous triple cancer of the pancreas, esophagus, and lung. While the esophageal and lung cancer were relatively non-progressive, the pancreatic tail cancer had invaded the aorta, celiac axis, and left kidney, and the patient was diagnosed with unresectable locally advanced disease. Because the described lesion could have been the prognostic determinant for this patient, we initiated intensive chemotherapy (gemcitabine plus nab-paclitaxel) for pancreatic cancer. After six courses of chemotherapy, the tumor size shrank remarkably and no invasion to the aorta or celiac axis was observed. No significant changes were observed in the esophageal and lung cancers; endoscopic submucosal dissection could be still a curative treatment for the esophageal cancer. Therefore, we performed curative resection for pancreatic cancer (distal pancreatomy, splenectomy, and left nephrectomy; ypT3N0cM0, ypStage IIA, UICC 8th). Pathologically, complete resection was achieved. The patient then underwent endoscopic submucosal dissection for early esophageal cancer (pT1a[M]-LPM) and video-assisted thoracoscopic right upper lobectomy in combination with right lower partial resection for early lung cancer (pT2aN0M0, pStage IB, UICC 8th). Eight months after pancreatic cancer surgery, the patient is alive and has no sign of recurrence; as a result of the successful treatment, the patient has a good quality of life. Conclusions Treatment of MPC is challenging, especially for cases with unresectable tumors. Although synchronous triple cancer can involve unresectable pancreatic cancer, radical resection may be possible after careful assessment of the appropriate treatment strategy and downstaging of unresectable tumors.